The Role of the Department Chair: A Replication and Extension - Watson, Roy E. L. (Canadian Journal of Higher Education, 1986)
This article reports the findings of a survey of faculty opinion which both replicated and extended an earlier study of the perception of the chairperson' s role at one university. Broad agreement now exists in the definition of this role. Social Scientists no longer hold views which conflict with those of their Natural Science and Humanist colleagues. This strong consensus is best explained by the shared experience of being administered by a bureaucracy established in response to the demands of the I960's for reform of university administration.